2022
DOI: 10.1155/2022/9448620
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging Studies of Chronic Prostatitis/Chronic Pelvic Pain Syndrome

Abstract: Evidence shows that chronic prostatitis/chronic pelvic pain syndrome hugely impacts the body and mind. The central mechanisms in patients with CP/CPPS resulted in increased attention as neuroimaging techniques developed. This review investigated the study design and major neuroimaging findings in CP/CPPS patients to provide comprehensive evidence. Seven databases were searched and screened: PubMed, EMBASE/SCOPUS, Cochrane Library Database, China National Knowledge Infrastructure, VIP, Wanfang, and China Biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
(28 reference statements)
0
6
0
1
Order By: Relevance
“…34 Another study found reciprocal relationships between pelvic pain and negative mood, such that negative mood changes directly corresponded with increased symptoms 2 weeks later and vice versa. 35 Interacting emotional and cognitive processes 36 are critical components of the pathophysiology of chronic pain as demonstrated by both clinical studies and a growing neuroimaging literature 37,38 that implicates cognitive control brain networks governing emotional and pain responses underlying UCPPS. For example, a recent prospective study demonstrated that increased connectivity in frontal parietal cognitive control networks predicted UCPPS pain reduction over 3 months, supporting the important role of cognitive factors modulating symptoms.…”
Section: The Science Of Pelvic Pain "Chronification"mentioning
confidence: 99%
“…34 Another study found reciprocal relationships between pelvic pain and negative mood, such that negative mood changes directly corresponded with increased symptoms 2 weeks later and vice versa. 35 Interacting emotional and cognitive processes 36 are critical components of the pathophysiology of chronic pain as demonstrated by both clinical studies and a growing neuroimaging literature 37,38 that implicates cognitive control brain networks governing emotional and pain responses underlying UCPPS. For example, a recent prospective study demonstrated that increased connectivity in frontal parietal cognitive control networks predicted UCPPS pain reduction over 3 months, supporting the important role of cognitive factors modulating symptoms.…”
Section: The Science Of Pelvic Pain "Chronification"mentioning
confidence: 99%
“…This technology has played a significant role in reshaping our understanding of chronic pain as a degenerative disease [ 22 ]. The findings of Zhao et al highlight the advancements in neuroimaging techniques that have shed light on brain alterations in individuals with chronic pain disorders such as chronic prostatitis/chronic pelvic pain syndrome and chronic low back pain [ 53 ]. Recent investigations into chronic prostatitis/chronic pelvic pain syndrome mechanisms have centered on elucidating crucial pathological features.…”
Section: Reviewmentioning
confidence: 99%
“…Betroffene zeigen eine lokale und überregionale Hypersensitivität. Wie auch bei anderen chronischen Schmerzsyndromen zeigt sich in der MRT-Bildgebung eine relative Reduktion der grauen Substanz im anterioren Zingulum 14 . Unklar bleibt es in den meisten Fällen, ob eine periphere Störung zu einer Dysfunktion des Schmerzsystems oder ob die Dysfunktion des Schmerzsystems zu einer peripheren Störung führt.…”
Section: Chronischer Beckenbodenschmerzunclassified